DETERMINANTS OF HIV/AIDS AWARENESS AND KNOWLEDGE IN TANAH PAPUA, INDONESIA - Elyda Akhya Afida Misrohmasari (UNEJ e-Proceeding)
Human Immunodeficiency Virus (HIV) infection hasbeen a major global health issue. HIV infection notonly affects the health of a population, but alsosignificantly impacts the economic and socialenvironment as well6. In Indonesia, the prevalenceof HIV infection among 15-49 year olds wasestimated around 0.4% in 20138. However, acrosstwo provinces in Tanah Papua, namely West Papuaand Papua, the epidemic was extremely high withHIV prevalence at 2.3% among general populationwhich categorized as a generalized populationepidemic level, based on WHO classification8. Thehigh HIV prevalence in Tanah Papua suggests theneed for prevention strategies that consider thelocal context. One of strategies for HIV preventionprograms is to assess HIV/AIDS knowledge ofpopulations14.Knowledge on HIV and AIDS is an importantprerequisite for the adoption of behaviouralchanges to prevent the risk of HIV transmission4.Assessing factors that contribute to the perceivedknowledge of HIV/AIDS is essential to prioritize anddeliver effective HIV prevention programs in TanahPapua. HIV knowledge has been shown to bedetermined by wider societal aspects such as,socioeconomic status, social networks andcommunity characteristics9,13. Understanding theassociation of these factors are important aspects toconsider when designing HIV prevention programs incommunities. Such studies can be useful forHIV/AIDS service providers better understand themechanism through which HIV/AIDS messages aretransmitted and received by individuals in thecommunity9.However, the literature on HIV/AIDS knowledge andits determinants in Tanah Papua, Indonesia is limiteddespite the relatively high prevalence of HIV inTanah Papua. Previous studies on socioeconomicfactors and HIV/AIDS knowledge in Indonesia are notcomprehensive and only focus on the associationbetween HIV/AIDS knowledge and individualsocioeconomic characteristics in risky populations.Additionally, no studies have investigated the linkbetween community socioeconomic characteristics,social capital and HIV/AIDS knowledge in theseprovinces.Therefore, the aim of this study is to assess HIV/AIDSawareness and knowledge and to examine anassociation between individual characteristics,community participation, community characteristicsand HIV/AIDS awareness and knowledge among 15years older in Tanah Papua Indonesia.